Legal Event of Death and Collected Taxes in the Czech Republic: Comparative Study - Hrubá Smržová, Petra; Hablovič, Jakub (Review of European and Comparative Law, 2025)
Taxes certainly belong amongst the biggest social phenomena. They affect all residents of the state and are constantly in the focus of interest of the general public. They include legal, economic, social, sociological psychological, and political aspects. Death as a legal event is connected with settlement of tax obligations stricto sensu of natural persons in the Czech Republic in connection with their death from a legal perspective.